An International Comparison of Enablers of Individual Readiness for Change: The Case of Executives Working in France, GCC and India - Saïd, Karim; Nair, Abhilash (Management international / International Management / Gestiòn Internacional, 2021)
The purpose of this paper is to examine the components that foster individual readiness for organizational change. To address this question, we conducted an international comparison of the perception of managers at different levels of organizational hierarchy. This research employed a quantitative survey research design administrated to two hundred and fifty-six employees, in different hierarchical levels in organizations, from France, GCC (Arab states of the Gulf Cooperation Council) and India enrolled in several executive training programs. Our research supports the idea the perception of the change process unlike the context of change is a significant determinant of employees’ readiness for change. The study controls for key individual antecedents of change readiness. Accordingly, we have shown that readiness for change may vary according to nationality and hierarchical position of an individual. We conclude that successful implementation of change cannot be reached without a need for change being established, which can be triggered and nurtured through the appropriate change management processes.